PERBANDINGAN NILAI PENDIDIKAN KEMANUSIAAN DALAM NOVEL PEREMPUAN BERKALUNG SORBAN KARYA ABIDAH EL KHALIEQY DAN FATIHAH CINTA KARYAAMIE EL FARABY - Dhanik Rokhilati (EDU-KATA, 2018)
The aims of this research are explaining and identification : (1) Education value of Perempuan Berkalung Sorban novel by Abidah El Khalieqy ; (2) Education value of Fatihah Cinta novel by Amie El Faraby ; This research is used kualitatif descriptive method. It is used to find many informations and datas from novel texts. Technique of collection datas use interactive technique and non interactive technique.This research find and identification : (1) the education values in Perempuan Berkalung Sorban novel are humanity education; (2) the education values in Fatihah Cinta novel are humanity education.